TINDAK TUTUR DIREKTIF DALAM VIDEO ANIMASI KISAH MUHAMMAD IBNU SIRIN - Alvia Hairunisa; Tatang Tatang (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2023)
In this study, the researcher refers to an animated Arabic video entitled "The Story of Muhammad Ibn Sirin". The video describes a tabi'in named Muhmmad Ibnu Sirin who was born in Medina in 33 Hijriyah. Illocutionary speech acts include statements (assertives), requests (directives), promises (commissives), expressions of feelings (expressives), and declarations (declaratives). This research uses a descriptive research type using a qualitative approach which will produce descriptive data in the form of a series of written words during the analysis stage, and the stage of presenting the results of the analysis. . Then the utterances contained in the video are listened to, data collection in the form of utterances containing directive speech acts is carried out by paying attention to the existing utterances. Based on the results of research that has been done, directive speech acts in the animated video The Story of Muhammad Ibnu Sirin have various functions. These functions are to order, prohibit, request, warn, question, expect, beg.